Rimegepant for the treatment of migraine - Amnon A. Berger; Ariel Winnick; Austin H. Carroll; Alexandra Welschmeyer; Nathan Li; Marc Colon; Antonella Paladini; Giovanni F. Ramírez; Jamal Hasoon; Elyse M. Cornett; Jaehong Song; Giustino Varrassi; et al. (Health Psychology Research)
Migraine is a common form of primary headache, affecting up to 1 in every 6 Americans. The pathophysiology is an intricate interplay of genetic factors and environmental influence and is still being elucidated in ongoing studies. The trigeminovascular system is now known to have a significant role in the initiation of migraines, including the release of pain mediators such as CGRP and substance P. Traditional treatment of migraine is usually divided into acute and preventive treatment. Acute therapy includes non-specific therapy, such as NSAIDs and other analgesics, which may provide relief in mild to moderate migraines. 5-HT1 agonists may provide relief in severe migraine, but are not universally effective and carry a significant side-effect profile with frequent redosing requirement. Prophylactic therapy may reduce the occurrence of acute migraine attacks in selected patients, but does not completely eliminate it. More recently, CGRP antagonism has been studied and shown to be effective in both abortion and prevention of migraine. Novel medications, targeting CGRP, divide into CGRP antibodies and receptor antagonists (gepants). Rimegepant, a second-generation gepant, has shown efficacy in several clinical trials in treating acute migraine. Ongoing trials are also evaluating its role in migraine prophylaxis, and results are promising. It is also generally safer for use than existing options, does not appear to increase the chance of developing chronic migraines, and carries a very tolerable side effects profile. It is a part of a growing arsenal in migraine treatment, and may present the silver bullet for treatment of this disease.